164k views
5 votes
I inserted a picture of the question, can you please make it very short CHECK ALL THAT APPLY

I inserted a picture of the question, can you please make it very short CHECK ALL-example-1
User Kayo
by
5.6k points

1 Answer

3 votes

We have the following expression:


3\sqrt[]{6}

since


\sqrt[]{9}=3

Our expression is equivalent to


\sqrt[]{9}\cdot\sqrt[]{6}

Additionally, we can note that


\sqrt[]{6}=\sqrt[]{2*3}=\sqrt[]{2}\cdot\sqrt[]{3}

Then, we can write


\begin{gathered} \sqrt[]{9}\cdot\sqrt[]{6}=\sqrt[]{9}\cdot\sqrt[]{2}\cdot\sqrt[]{3} \\ \text{which is equivalent to} \\ \sqrt[]{9\cdot3}\cdot\sqrt[]{2}=\sqrt[]{27}\cdot\sqrt[]{2} \end{gathered}

And finally, we can note that


\sqrt[]{27}\cdot\sqrt[]{2}=\sqrt[]{27*2}=\sqrt[]{54}

Therefore, the answers are:


\begin{gathered} \sqrt[]{9}\cdot\sqrt[]{6} \\ \\ \sqrt[]{27}\cdot\sqrt[]{2} \\ \\ \sqrt[]{54} \end{gathered}

User Whoughton
by
6.4k points